Subjective Socioeconomic Status, Cognitive Abilities, and Personal Control: Associations With Health Behaviours - Kraft, Pål; Kraft, Brage; Hagen, Thomas; Espeseth, Thomas (Frontiers in Psychology, 2022)
Objective To examine subjective and objective socioeconomic status (SSES and OSES, respectively) as predictors, cognitive abilities as confounders, and personal control perceptions as mediators of health behaviours. Design A cross-sectional study including 197 participants aged 30–50 years, recruited from the crowd-working platform, Prolific. Main Outcome Measure The Good Health Practices Scale, a 16-item inventory of health behaviours. Results SSES was the most important predictor of health behaviours (beta = 0.19, p < 0.01). Among the OSES indicators, education (beta = 0.16, p < 0.05), but not income, predicted health behaviours. Intelligence (r = −0.16, p < 0.05) and memory (r = −0.22, p < 0.01) were negatively correlated with health-promoting behaviours, and the effect of memory was upheld in the multivariate model (beta = −0.17, p < 0.05). Personal control perceptions (mastery and constraints) did not act as mediators. Conclusion SSES predicted health behaviours beyond OSES. The effect of socioeconomic indicators was not confounded by cognitive abilities. Surprisingly, cognitive abilities were negatively associated with health-promoting behaviours. Future research should emphasise SSES as a predictor of health behaviours. Delineating the psychological mechanisms linking SSES with health behaviours would be a valuable contribution toward improved understanding of socioeconomic disparities in health behaviours.